Managing Education and Training for Electronic Medical Records to Improve Medical Service Quality at Gunung Maria General Hospital, Tomohon - Rizki R. Najoan; Mozes M. Wullur; Rolles N. Palilingan; Ruth Umbase (JR Education, 2026)
The digitalization of health services has shifted hospital management toward integrated information systems, more accurate data governance, and stronger human resource capability. One of the most consequential changes in this transition is the adoption of Electronic Medical Records (EMR), which replaces fragmented paper-based documentation with digital records that can support continuity of care, patient safety, and managerial efficiency. Yet the success of EMR implementation depends not only on software and infrastructure but also on how hospitals manage education and training for the personnel who use the system. This article develops a journal-style synthesis of a qualitative dissertation on the management of EMR training at Gunung Maria General Hospital, Tomohon, Indonesia. The study focused on four managerial dimensions: planning, organizing, implementation, and evaluation of training. Using a qualitative descriptive design, data were gathered through in-depth interviews, observations, and document analysis involving hospital management, medical personnel, and administrative staff. The findings show that EMR utilization has been constrained by high rates of input error, uneven user competence, inadequate needs analysis, limited continuity in post-training support, and weak supervision and evaluation mechanisms. Although EMR training has been implemented, it has not yet been managed as a systematic competency-based program grounded in continuous improvement. The study further shows that effective EMR utilization requires alignment between training design, organizational support, workflow integration, supervision, and evaluation. Based on these findings, the article proposes an integrated education and training management model that emphasizes competency mapping, adaptive instructional strategies, structured mentoring, ongoing supervision, and periodic evaluation linked to service quality outcomes. The model is expected to reduce human error, improve the accuracy of medical data, strengthen user confidence, and enhance the quality of care. This article contributes to educational management and health information systems literature by demonstrating that digital transformation in hospitals must be supported by a human-centered training system rather than by technology adoption alone.